Radiation shielding method and radiation shielding body based on multi-physics field synergistic effect
The three-layer shielding structure with multi-physics synergy effect solves the dynamic shielding requirements of neutron-gamma mixed radiation field in BNCT treatment scenarios, achieves efficient radiation shielding effect, reduces weight and cost, and improves material durability.
Patent Information
- Application Number
- CN202511040850.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-25
- Publication Date
- 2025-11-04
AI Technical Summary
Traditional shielding devices are difficult to adapt to the dynamic shielding requirements of neutron-gamma mixed radiation fields in BNCT treatment scenarios, resulting in insufficient shielding capabilities and uncertainties in shielding effectiveness and the risk of secondary radiation.
A radiation shielding method based on the synergistic effect of multiphysics fields is adopted. Through a three-layer shielding structure, the first layer preferentially absorbs thermal neutrons and low-energy gamma rays, the second layer attenuates gamma rays through a gradient-decreasing concentration of nano-barium sulfate, and the third layer extends the gamma ray path. By utilizing the synergistic effect of nano-ferrites, energy attenuation matching and dynamic shielding are achieved.
It effectively shields the complex radiation composition in the neutron-gamma mixed radiation field, reduces the self-weight and construction cost of traditional shielding bodies, solves the uncertainty problem of the secondary radiation shielding effectiveness of traditional boron and lithium concrete, and improves shielding efficiency and material durability.
Smart Images

Figure CN120895284A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of radiation shielding in the neutron therapy scene, in particular to a radiation shielding method and a radiation shielding body based on the synergistic effect of multiple physical fields. BACKGROUND
[0002] In recent years, BNCT boron neutron capture therapy has been promoted and applied in some countries in the world as the core of tackling the treatment problem of malignant tumors. BNCT has the advantages of high space utilization rate and low investment cost, but the radiation protection of the shielding room is still a major industry problem.
[0003] During the treatment of BNCT, various types of shielding bodies in the shielding room need to be able to meet the dynamic shielding requirements of the neutron-gamma mixed radiation field. Taking the shielding wall as an example, the traditional shielding wall is mostly a concrete wall, which often uses heavy aggregates and special cement to increase the density and enhance the shielding ability of gamma rays and neutrons. However, for the thermal and fast neutrons in the neutron radiation field under the BNCT treatment scene, the shielding effect is limited. If the thickness of the shielding wall is increased, the self-weight of the wall will be too large, which will require strengthening the building structure, increasing the construction difficulty and construction cost. In addition, there is a high risk of secondary radiation, which requires additional protection measures. The shielding efficiency is uncertain and it is difficult to adapt to the dynamic shielding requirements of the neutron-gamma mixed radiation field. SUMMARY
[0004] The present application aims to provide a radiation shielding method and a radiation shielding body based on the synergistic effect of multiple physical fields to solve the technical problem that the traditional anti-radiation shielding body is difficult to adapt to the dynamic shielding requirements of the neutron-gamma mixed radiation field under the BNCT treatment scene, resulting in insufficient shielding ability.
[0005] To solve the above technical problems, the present application adopts the following technical solutions:
[0006] In a first aspect, the present application provides a radiation shielding method based on the synergistic effect of multiple physical fields for shielding a neutron-gamma mixed radiation field, characterized in that it comprises:
[0007] In a first stage, the first composite material absorbs neutrons and gamma rays at the initial position of radiation;
[0008] In a second stage, the second composite material implements energy spectrum adaptation attenuation on the first remaining radiation after the first stage, and the amount of the second composite material decreases gradiently along the radiation propagation direction;
[0009] In a third stage, the third composite material implements path scattering on the second remaining radiation after the second stage.
[0010] The first stage can absorb thermal neutrons and low-energy gamma rays by the first composite material. In the second stage, the amount of the second composite material decreases along the radiation propagation direction, which can make the relatively high concentration area produce Compton scattering energy reduction effect on high-energy gamma rays of 1-3 MeV, trigger the electron pair effect to absorb high-energy gamma rays of 5-10 MeV in the medium concentration area, and absorb secondary X-rays of 30-300 keV generated by bremsstrahlung. In the third stage, the second remaining radiation, mainly gamma rays, prolongs the scattering path and further reduces the energy. The three stages work together to effectively shield the complex radiation composition generated in the neutron-gamma mixed radiation field.
[0011] Preferably, the first composite material comprises a radiation shielding agent and a neutron absorber; and the mass ratio of the radiation shielding agent to the neutron absorber in the first composite material ranges from 10:1 to 45:1.
[0012] Specifically, the radiation shielding agent is used to absorb gamma rays and slow down fast neutrons into thermal neutrons, and the neutron absorber is used to absorb thermal neutrons and trigger neutron capture reaction to reduce the initial radiation intensity.
[0013] Preferably, the second composite material comprises the radiation shielding agent and nano-ferrite; the nano-ferrite can be coupled to the surface of the radiation shielding agent; and the mass ratio of the radiation shielding agent to the nano-ferrite in the second composite material ranges from 5:1 to 8:1.
[0014] Preferably, the third composite material comprises the radiation shielding agent and scattering fibers; and the mass ratio of the radiation shielding agent to the scattering fibers in the third composite material ranges from 10:1 to 30:1.
[0015] Preferably, the radiation shielding agent is selected from one of barite, nano-barium sulfate particles, or modified nano-barium sulfate particles.
[0016] Preferably, the neutron absorber is selected from one of inorganic boron salt, boron-containing organic matter, or boron fiber. Preferably, the boron fiber can enhance the structural strength of the first shielding layer in addition to capturing boron neutrons.
[0017] Preferably, the nano-ferrite is a modified nano-particle obtained after surface modification by a surface modifier; and the surface modifier is one of polydopamine PDA, silane coupling agent, polyvinylpyrrolidone, and hexagonal boron nitride. The modified nano-ferrite particle can be directionally combined with the lattice defect sites of the radiation shielding agent to form a three-dimensional conductive network, accelerate charge dissipation, and improve the gamma shielding efficiency, neutron shielding efficiency, secondary radiation dose rate, and crack toughness.
[0018] In a second aspect, the present application provides a radiation shielding method based on the synergistic effect of multiple physical fields, comprising a first shielding layer, a second shielding layer and a third shielding layer arranged in sequence along the direction of radiation propagation.
[0019] The first shielding layer, the second shielding layer and the third shielding layer are respectively doped with the first composite material, the second composite material and the third composite material.
[0020] The first composite material comprises a radiation shielding agent and a neutron absorber.
[0021] The second composite material comprises the radiation shielding agent and nano ferrite.
[0022] The third composite material comprises the radiation shielding agent and scattering fibers.
[0023] The second shielding layer is a multi-layer structure, each layer structure is doped with the second composite material, and the doping amount of the second composite material in each layer structure decreases gradually along the direction of radiation propagation.
[0024] In this scheme, the radiation shielding body is provided with a gradient-decreasing radiation shielding agent, which can realize energy attenuation matching, and also has a multi-physical field synergistic mechanism. The neutron shielding gradient is: boron (first shielding layer) → nano ferrite (second shielding layer) → scattering fibers (third shielding layer), which forms a continuous capture-moderation-scattering chain. The electromagnetic field regulation: nano ferrite absorbs the secondary X-rays generated by bremsstrahlung through domain wall resonance. Moreover, the second shielding layer is arranged as a multi-layer structure, and the concentration of the radiation shielding agent decreases, which can change the refractive index of the radiation in each layer, thereby increasing the attenuation time of the radiation in the second shielding layer and further reducing the radiation.
[0025] Preferably, in the first shielding layer, the first doping amount of the radiation shielding agent ranges from 32 to 44 wt%, and the mass ratio of the radiation shielding agent to the neutron absorber ranges from 10:1 to 45:1.
[0026] In the second shielding layer, the nano ferrite can be coupled to the surface of the radiation shielding agent; the doping amount of the radiation shielding agent in the first layer of the second shielding layer close to the first shielding layer is less than or equal to the first doping amount; in each layer structure of the second shielding layer, the doping amount of the radiation shielding agent in two adjacent layer structures changes by a gradient rate of ≤5 wt% per cm, and the mass ratio of the radiation shielding agent to the nano ferrite ranges from 5:1 to 8:1.
[0027] The second doping amount of the radiation-proof agent in the third shielding layer is 20-30wt%, and the mass ratio of the radiation-proof agent to the scattering fiber is 10:1-30:1; the first doping amount is greater than the second doping amount, and the doping amount of the radiation-proof agent in the last layer of the second shielding layer close to the third shielding layer is greater than or equal to the second doping amount.
[0028] Preferably, the thickness of the first shielding layer is 0-10cm, and the thickness of the second shielding layer is 10-30cm, and correspondingly, the second shielding layer has a total number of layers n of 5-20 layers, and the thickness of the third shielding layer is greater than or equal to 30cm. Within a certain thickness range, the appropriate number of layers of the second shielding layer can be set, so that a better shielding effect can be obtained, and the construction cost can be maintained low.
[0029] The radiation shielding method based on the multi-physical field synergistic effect has the following beneficial effects: the radiation shielding method based on the multi-physical field synergistic effect disclosed in the application includes three synergistic shielding stages, in the first stage, the first composite material can preferentially absorb thermal neutrons and low-energy gamma rays, in the second stage, the amount of the second composite material decreases along the radiation propagation direction, so that the Compton scattering energy reduction effect of high-energy gamma rays with a wavelength of 1-3MeV is generated in the relatively high concentration area, the electron pair effect is triggered to absorb high-energy gamma rays with a wavelength of 5-10MeV in the medium concentration area, and the secondary X-rays with a wavelength of 30-300keV generated by the bremsstrahlung radiation are also absorbed, in the third stage, the path of the second remaining radiation, mainly gamma rays, is prolonged to further reduce the energy, and the three stages synergistically shield the complex radiation composition generated in the neutron-gamma mixed radiation field; the application can adapt to the dynamic shielding requirements of the neutron-gamma mixed radiation field, and solve the uncertainty problem of the secondary radiation shielding efficiency of the traditional boron and lithium concrete by utilizing the synergistic effect of the nanometer ferrite. BRIEF DESCRIPTION OF DRAWINGS
[0030] In order to make the purpose, technical scheme and advantages of the application more clear, the application will be further described in detail below with reference to the drawings, in which:
[0031] Figure 1 The flow chart of the radiation shielding method based on the multi-physical field synergistic effect. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings. Obviously, the described embodiments are only some of the embodiments of the present application, but not all of the embodiments. Based on the embodiments provided by the present application, all other embodiments obtained by those of ordinary skill in the art are within the scope of protection of the present application. It should be noted that, in the drawings with reference numerals, the same reference numerals and letters represent similar components, and once a component is defined in one drawing, it will not be repeatedly defined and explained in subsequent drawings.
[0033] The present application can be applied to a neutron-gamma mixed radiation field including a BNCT treatment scene, can effectively shield neutrons and gamma radiation, and solves the technical problem that a conventional radiation shielding body is difficult to adapt to the dynamic shielding demand of a neutron-gamma mixed radiation field when facing the neutron-gamma mixed radiation field generated in the BNCT treatment scene, resulting in insufficient shielding capacity.
[0034] The technical concept of the present application is that, taking a shielding wall as an example, a conventional shielding wall is mostly a concrete wall, and heavy aggregate and special cement are often used to improve the density and enhance the shielding capacity for gamma rays and neutrons, but the shielding effect is limited for thermal neutrons and fast neutrons in the neutron radiation field in the BNCT treatment scene; if the thickness of the shielding wall is increased, the self-weight of the wall will be too large, the building structure needs to be strengthened, the construction difficulty and construction cost are increased, and in addition, secondary radiation may be caused, and the shielding efficiency is uncertain, which is difficult to adapt to the dynamic shielding demand of the neutron-gamma mixed radiation field.
[0035] It should be noted that the present application takes a radiation shielding wall as an example to describe the technical concept, but the method of the present application is not limited to being applied to the radiation shielding wall, and can also be applied to other radiation shielding scenes with a neutron-gamma mixed radiation field.
[0036] The present application designs a radiation shielding method based on the synergistic effect of multiple physical fields, and redesigns the structure of the shielding wall based on the method, and three shielding layers are provided, the side close to the radiation generation preferentially absorbs thermal neutrons and low-energy gamma rays; the middle layer can effectively attenuate gamma rays by gradient control of the concentration of nano-barium sulfate, avoid the risk of local penetration of high-energy photons caused by a single material, and solve the problem of secondary radiation by using the synergistic effect of nano-ferrite; the third layer can prolong the path of gamma rays; the present application can adapt to the dynamic shielding demand of the neutron-gamma mixed radiation field, avoids the disadvantages of heavy weight and high cost of homogeneous barite concrete, and solves the uncertainty problem of the secondary radiation shielding efficiency of the conventional boron and lithium concrete by using the synergistic effect of nano-ferrite.
[0037] In addition, the applicant finds that when nano-barium sulfate and nano-ferrite are simultaneously added in the intermediate layer, agglomeration is prone to occur, and it is difficult to uniformly disperse each material in the intermediate layer, which affects the shielding effect. The present application also modifies the nano-barium sulfate and the nano-ferrite respectively, so that the nano-ferrite particles can be coupled to the surface of the nano-barium sulfate particles, thereby solving the technical problem of agglomeration of nano-barium sulfate and nano-ferrite.
[0038] In order to further illustrate the method of the present application, the following embodiments are disclosed.
[0039] In some embodiments, referring to Figure 1 The present application provides a radiation shielding method based on the synergistic effect of multiple physical fields, which is used for shielding a neutron-gamma mixed radiation field, and has the characteristics that it comprises:
[0040] In the first stage, the first composite material absorbs neutrons and gamma rays at the initial position of radiation;
[0041] In the second stage, the second composite material performs energy spectrum adaptation attenuation on the first residual radiation after the first stage, and the amount of the second composite material decreases along the radiation propagation direction.
[0042] In the third stage, the third composite material performs path scattering on the second residual radiation after the second stage.
[0043] Specifically, the neutron-gamma mixed radiation field includes thermal neutrons, fast neutrons, low-energy gamma rays, high-energy gamma rays, and secondary X-rays. Among them, the fast neutron refers to a neutron with an energy range of 0.1 MeV to 40 MeV, the thermal neutron refers to a neutron with an energy range of 0.01 eV to 0.1 eV, and its most probable value is about 0.0253 eV, the low-energy gamma ray refers to a ray with an energy range of <100 keV, including characteristic X-rays and soft gamma rays, the high-energy gamma ray refers to a ray with an energy range of 1 MeV to 10 MeV, and the secondary X-ray refers to an X-ray generated by bremsstrahlung radiation.
[0044] In the first stage, the first composite material preferentially absorbs thermal neutrons and low-energy gamma rays. In the second stage, the amount of the second composite material decreases along the radiation propagation direction, which can cause Compton scattering energy reduction effect on 1-3 MeV high-energy gamma rays in the relatively high concentration area, trigger electron pair effect to absorb 5-10 MeV high-energy gamma rays in the medium concentration area, and absorb 30-300 keV secondary X-rays generated by bremsstrahlung radiation. In the third stage, the second residual radiation is mainly gamma rays, which prolongs the scattering path and further reduces the energy. The synergistic effect of the three stages effectively shields the complex radiation components generated in the neutron-gamma mixed radiation field.
[0045] In some embodiments, the radiation shielding method based on the synergistic effect of multiple physical fields can be applied to shielding walls, shielding plates, large or small shielding components, and any other scene with mixed neutron-gamma radiation fields.
[0046] In some embodiments, the first composite material includes a radiation shielding agent and a neutron absorber; and the mass ratio of the radiation shielding agent to the neutron absorber in the first composite material ranges from 10:1 to 45:1.
[0047] Specifically, the radiation shielding agent is used to absorb gamma rays and slow down fast neutrons into thermal neutrons, and the neutron absorber is used to absorb thermal neutrons and trigger neutron capture reactions to reduce the initial radiation intensity.
[0048] In some embodiments, the second composite material includes the radiation shielding agent and nano-ferrite; the nano-ferrite can be coupled to the surface of the radiation shielding agent; and the mass ratio of the radiation shielding agent to the nano-ferrite in the second composite material ranges from 5:1 to 8:1.
[0049] In some embodiments, the third composite material includes the radiation shielding agent and scattering fibers; and in some embodiments, the radiation shielding agent is selected from one of barite, nano-barium sulfate particles, or modified nano-barium sulfate particles.
[0050] In some embodiments, the neutron absorber is selected from one of inorganic boron salts, boron-containing organic matter, or boron fibers. Boron fibers are preferred, which can enhance the structural strength of the first shielding layer in addition to capturing boron neutrons.
[0051] In some embodiments, the nano-ferrite is a modified nano-particle obtained after surface modification; and the surface modifier is one of polydopamine PDA, silane coupling agent, polyvinylpyrrolidone, and hexagonal boron nitride. The modified nano-ferrite particles can be directionally combined with the lattice defect sites of the radiation shielding agent to form a three-dimensional conductive network, accelerate charge dissipation, and improve the gamma shielding efficiency, neutron shielding efficiency, secondary radiation dose rate, and crack toughness.
[0052] In some embodiments, a radiation shield is also provided, which is built by using the above-mentioned radiation shielding method based on the synergistic effect of multi-physical fields, comprising a first shielding layer, a second shielding layer and a third shielding layer arranged in sequence along the direction of radiation propagation; the first shielding layer, the second shielding layer and the third shielding layer are respectively doped with the first composite material, the second composite material and the third composite material; the first composite material comprises a radiation protection agent and a neutron absorber; the second composite material comprises the radiation protection agent and nano ferrite; the third composite material comprises the radiation protection agent and scattering fibers; the second shielding layer is a multi-layer structure, each layer structure is doped with the second composite material, and the doping amount of the second composite material in each layer structure decreases gradually along the direction of radiation propagation. In this scheme, the radiation shield is provided with a gradient-decreasing radiation protection agent, which can achieve energy attenuation matching, and also has a multi-physical field synergistic mechanism. The neutron shielding gradient is: boron (first shielding layer) → nano ferrite (second shielding layer) → scattering fibers (third shielding layer) to form a continuous capture-slowing-scattering chain; electromagnetic field regulation: nano ferrite absorbs secondary X-rays generated by bremsstrahlung through domain wall resonance. Moreover, the second shielding layer is arranged as a multi-layer structure, and the concentration of the radiation protection agent decreases, which can change the refractive index of the radiation in each layer, thereby increasing the attenuation time of the radiation in the second shielding layer and further reducing the radiation. The present application can adapt to the dynamic shielding requirements of the neutron-gamma mixed radiation field, realize the technical effects of preferentially absorbing thermal neutrons by the first shielding layer, inhibiting bremsstrahlung by the second shielding layer, and scattering gamma rays by the third shielding layer, avoid the shortcomings of heavy weight and high cost of homogeneous barite concrete, and solve the uncertainty problem of the shielding efficiency of secondary radiation of traditional boron and lithium concrete by using the synergistic effect of nano ferrite.
[0053] In some embodiments, in the first shielding layer, the first doping amount of the radiation protection agent ranges from 32wt% to 44wt%, and the mass ratio of the radiation protection agent to the neutron absorber ranges from 10:1 to 45:1.
[0054] In the second shielding layer, the nano ferrite can be coupled to the surface of the radiation protection agent; the doping amount of the radiation protection agent in the first layer of the second shielding layer close to the first shielding layer is less than or equal to the first doping amount; in each layer structure of the second shielding layer, the doping amount of the radiation protection agent in adjacent two layer structures changes by a gradient change rate ≤5wt% / cm, and the mass ratio of the radiation protection agent to the nano ferrite ranges from 5:1 to 8:1; the corresponding proportion of nano ferrite in the second shielding layer is 2wt% to 5wt%. Under this parameter range, better radiation shielding effect can be achieved.
[0055] The second doping amount of the radiation shielding agent in the third shielding layer is 20-30wt%, and the mass ratio of the radiation shielding agent to the scattering fiber is 10:1-30:1; the first doping amount is greater than the second doping amount, and the doping amount of the radiation shielding agent in the last layer of the second shielding layer close to the third shielding layer is greater than or equal to the second doping amount.
[0056] Under the above value range of the embodiment, the radiation shielding effect is experimentally verified, and the results are shown in Table 1 below:
[0057] Table 1: Radiation shielding effect corresponding to the content of each parameter
[0058]
[0059] In some embodiments, the thickness of the first shielding layer is 0-10cm, the thickness of the second shielding layer is 10-30cm, and correspondingly, the second shielding layer has a total number of layers n of 5-20 layers, and the thickness of the third shielding layer is ≥30cm. Within a certain thickness range, setting an appropriate number of layers of the second shielding layer can not only obtain a better shielding effect, but also maintain a lower construction cost.
[0060] In some embodiments, as a preferred, the radiation shielding body is a concrete wall.
[0061] Specifically, the wt% refers to the mass percentage.
[0062] Specifically, the first doping amount refers to the mass percentage of the radiation shielding agent in the first shielding layer, and the second doping amount refers to the mass percentage of the radiation shielding agent in the third shielding layer.
[0063] In some embodiments, the boron doped in the first shielding layer is one of an inorganic salt of boron, a boron-containing organic matter, or a boron fiber.
[0064] In some embodiments, the second shielding layer uses an array of pneumatic nozzles to achieve spatial continuous variation of the doping amount of nano-barium sulfate, and the gradient accuracy of the second shielding layer is ±0.8wt%;
[0065] In some embodiments, the second shielding layer has a total number of layers n≥10. The more layers the second shielding layer has, the more times the radiation is refracted, and the better the shielding effect.
[0066] In some embodiments, the anti-radiation agent is preferably nano-barium sulfate particles, the neutron absorber is preferably boron fiber, the first doping amount is 38wt%, the second doping amount is 25wt%, the nano-barium sulfate particles in each layer of the second shielding layer are gradually decreased from 38wt% to 25wt%, and the mass ratio of nano-barium sulfate to nano-ferrite in each layer of the second shielding layer ranges from 7:1. Under this parameter range, a better radiation shielding effect can be achieved. The energy attenuation matching principle of the present embodiment is explained as follows:
[0067] The first shielding layer (high nano-barium sulfate concentration): using the high density characteristics of 38wt% barium sulfate, preferentially absorbing thermal neutrons and low energy gamma rays, reducing the initial radiation intensity through neutron capture reaction (10B+n→ 7 Li+α);
[0068] The second shielding layer (gradient decrease): the nano-barium sulfate doping amount is linearly decreased from 38% to 25wt%, corresponding to the attenuation curve of gamma ray energy with penetration depth, avoiding the risk of local penetration of high-energy photons caused by a single material;
[0069] The third shielding layer (stable low doping amount): 25wt% nano-barium sulfate maintains the basic shielding ability, combined with high-density boron-containing polyethylene fiber to form a porous structure, and prolongs the path of gamma rays through Compton scattering.
[0070] In some embodiments, the boron doped in the first shielding layer is preferably boron fiber, which can enhance the structural strength of the first shielding layer in addition to capturing boron neutrons. In practical applications, ultrasonic vibration realizes the horizontal layer orientation arrangement (orientation degree > 85%), which improves the neutron capture cross section by 1.3 times;
[0071] In some embodiments, the fiber added in the third shielding layer is high-density boron-containing polyethylene fiber.
[0072] In some embodiments, the thickness of the first shielding layer ranges from 0 to 10cm, the thickness of the second shielding layer ranges from 10 to 30cm, and the thickness of the third shielding layer is greater than or equal to 30cm.
[0073] In some embodiments, the first shielding layer further comprises nano-SiO2, which is used to fill micro-cracks and improve the interlayer shear strength.
[0074] In some embodiments, an optimal embodiment and technical effect are given. The fiber in the third shielding layer is high-density boron-containing polyethylene fiber, and the thickness of each shielding body, the doping amount of each component and the function are shown in Table 2 as follows.
[0075] Table 2 Gradient impedance matching structure (wt%)
[0076]
[0077] In this embodiment, in addition to setting the gradient-decreasing nano-barium sulfate to achieve energy attenuation matching, there is also a multi-physical field synergistic mechanism, and the neutron shielding gradient is: boron fiber (first shielding layer) → nano-ferrite (second shielding layer) → high-density boron-containing polyethylene fiber (third shielding layer) to form a continuous capture-moderation-scattering chain; electromagnetic field regulation: nano-ferrite absorbs secondary X-rays generated by bremsstrahlung through domain wall resonance, and the actual measurement can reduce secondary radiation by 42%.
[0078] In this embodiment, the performance advantages of the radiation shielding body configured in Table 1 and the traditional scheme are compared as shown in Table 3.
[0079] Table 3 Performance advantage analysis
[0080] Indicator Gradient structure scheme Homogeneous concrete scheme Thermal neutron absorption rate 96.2% (at 10 cm) 83.5% Secondary X-ray yield 0.12 photons / cm 3 ]] 0.38 photons / cm 3 ]] 250 keV gamma-ray attenuation coefficient 1.48 cm -1 ]] 1.12 cm -1 ]] Stress concentration factor 1.05 1.32
[0081] It can be seen that the design realizes the directional enhancement of material performance through gradient matching, which can reduce the wall thickness by 14% and improve the service life by 2.3 times compared with the traditional homogeneous structure.
[0082] In some embodiments, as preferred, the nano-barium sulfate and the nano-ferrite are both modified nanoparticles obtained after modification by a surface modifier, and the surface modifier is one of polydopamine PDA, silane coupling agent, polyvinylpyrrolidone, and hexagonal boron nitride. The modified Fe3O4 particles can be combined with the lattice defect sites of nano-barium sulfate, forming a three-dimensional conductive network, accelerating charge dissipation, and improving the gamma shielding efficiency, neutron shielding efficiency, secondary radiation dose rate, and crack toughness. This embodiment can solve the technical problem of agglomeration of nano-barium sulfate and nano-ferrite Fe3O4. The reason for the agglomeration of nano-barium sulfate (nano-barium sulfate) and nano-ferrite Fe3O4 is that the specific surface area of nano-barium sulfate (nano-barium sulfate) reaches 80-120 m 2 / g, the high surface energy leads to the enhancement of inter-particle van der Waals force, and it is easy to form hard agglomerates (diameter > 200 nm); nano-ferrite (Fe3O4) is prone to chain aggregation during preparation due to magnetic dipole interaction.
[0083] As preferred, the particle size of the nano-barium sulfate particles and the nano-ferrite particles is 50-100 nm.
[0084] The surface modifier is respectively used for surface modification of nano-barium sulfate and nano-ferrite, which can form -Si-O- bond network on the surface of nano-barium sulfate, so that the diameter of the agglomerate is reduced to below 50 nm, and the surface modifier can be wrapped around the surface of nano-ferrite particles to form a 2-5 nm physical barrier layer, so that the diameter of the agglomerate is reduced to 30±5 nm.
[0085] Preferably, the surface modifier for modifying nano-barium sulfate is preferably silane coupling agent KH550, and the surface modifier for modifying nano-ferrite is preferably polyvinylpyrrolidone (PVP).
[0086] In this embodiment, the synergistic effect mechanism between nano-barium sulfate and nano-ferrite Fe3O4 is as follows: magnetic nanoparticles form a local magnetic field through magnetic dipole interaction, which produces a Lorentz force on charged particles (such as beta rays) to deflect the trajectory and prolong the residence time in the material. The Bremsstrahlung radiation generated after neutron capture produces magnetic hysteresis loss by Fe3O4, which significantly reduces the secondary X-ray yield; the surface-modified nano-ferrite can adsorb free radicals generated by ionizing radiation to inhibit the chain reaction.
[0087] Meanwhile, an electric dipole layer (potential difference up to 0.35 V) is formed at the interface between nano-barium sulfate and nano-ferrite Fe3O4, which produces an interface polarization effect. The difference between the dielectric constant of nano-barium sulfate (ε≈6.2) and that of Fe3O4 (ε≈80) is large, forming a dielectric discontinuous zone at the interface, enhancing the local electric field strength, and electrons transfer from Fe3O4 to nano-barium sulfate, forming a built-in electric field (direction: Fe3O4→nano-barium sulfate). The interface electric field makes the charged particle (such as beta ray) move in a Larmor precession, prolonging the path and increasing the energy deposition probability. The electron cloud distortion at the polarization interface increases the gamma ray scattering cross section, enhances the Compton scattering cross section of gamma rays, and the measured 250 keV gamma ray attenuation coefficient is increased to 1.53 cm -1 (about 1.2 cm -1 for conventional materials); the modified nano-ferrite Fe3O4 particles can be directionally combined with the lattice defect sites of nano-barium sulfate to form a three-dimensional conductive network, accelerating the dissipation of electric charge.
[0088] Performance comparison and verification, as shown in the following Table 4.
[0089] Table 4 Performance comparison and verification
[0090]
[0091] The synergistic effect realizes the breakthrough of radiation shielding performance and material durability through multi-dimensional effects such as complementary energy absorption paths, interface polarization enhancement, and redox catalysis.
[0092] In some embodiments, as preferred, in-situ composite technology is adopted: introducing graphene carrier (loading 0.5-1.2wt%) in the stage of nano-barium sulfate synthesis, and isolating nanoparticles by virtue of its two-dimensional structure.
[0093] In some embodiments, a method for constructing a radiation shield is also provided, comprising the following steps:
[0094] S1, calculating the doping amount of nano-barium sulfate in each layer of the second shielding layer and the corresponding doping amount of nano-ferrite in each layer;
[0095] S2, configuring the second material ratio for constructing the second shielding layer according to the doping amount of nano-barium sulfate in each layer of the second shielding layer and the corresponding doping amount of nano-ferrite in each layer obtained in step S1;
[0096] S3, after mixing according to the second material ratio, layering according to the doping amount of nano-barium sulfate in each layer of the second shielding layer and the corresponding doping amount of nano-ferrite in each layer, and then vibrating uniformly and solidifying to obtain the second shielding layer;
[0097] S4, respectively configuring the first material ratio for constructing the first shielding layer and the third material ratio for constructing the third shielding layer, and respectively mixing according to the first material ratio and the third material ratio;
[0098] S5, constructing the first shielding layer on the side of the second shielding layer facing the radiation generation by using the mixed first material, and constructing the second shielding layer on the side of the second shielding layer away from the radiation generation by using the mixed third material, to obtain the radiation shield.
[0099] Specifically, in step S5, the mixed first material is vacuum sprayed on the surface of the side of the second shielding layer facing the radiation generation to obtain the first shielding layer, and the mixed third material is vacuum sprayed on the surface of the side of the second shielding layer away from the radiation generation to obtain the second shielding layer.
[0100] In some embodiments, it further comprises step S6, curing the first shielding layer, the second shielding layer and the third shielding layer, and filling nano-SiO2 sol in micro-cracks to improve shear strength, to obtain the radiation shield.
[0101] Specifically, the first material ratio, the second material ratio and the third material ratio respectively comprise: cementitious material, anti-radiation functional component, aggregate, admixture, and clean water.
[0102] The cementitious material comprises Portland cement, and the water-binder ratio of the Portland cement and the clean water is 0.32-0.35.
[0103] The first material ratio of the anti-radiation functional component includes modified nano-barium sulfate, and the doping amount of the modified nano-barium sulfate in the first material ratio ranges from 32wt% to 44wt%.
[0104] The second material ratio of the anti-radiation functional component includes modified nano-ferrite and modified nano-barium sulfate.
[0105] The third material ratio of the anti-radiation functional component includes modified nano-barium sulfate, and the doping amount of the modified nano-barium sulfate in the third material ratio ranges from 20wt% to 30wt%.
[0106] Specifically, the radiation shielding body is a concrete wall.
[0107] In some embodiments, preferably, in step S1, calculating the doping amount of nano-barium sulfate in each layer of the second shielding layer and the doping amount of nano-ferrite in each layer corresponding to the doping amount of nano-barium sulfate includes the following steps:
[0108] S1.1, constructing a simulation model of a radiation field and a radiation shielding body;
[0109] S1.2, constructing a gradient parameter optimization model and an optimized ratio model;
[0110] S1.3, inputting a preset thickness and number of layers of the second shielding layer into the gradient parameter optimization model to obtain an optimal gradient slope of the doping amount of nano-barium sulfate and to obtain the doping amount of nano-barium sulfate in each layer of the second shielding layer;
[0111] S1.4, inputting the doping amount of nano-barium sulfate in each layer of the second shielding layer into the simulation model in step S1.1 to predict a specific energy spectrum characteristic of each layer of the second shielding layer;
[0112] S1.5, inputting the predicted specific energy spectrum characteristic of each layer of the second shielding layer into the optimized ratio model to obtain an optimal mass ratio of nano-barium sulfate to nano-ferrite in each layer of the second shielding layer;
[0113] S1.6, inputting the optimal mass ratio of nano-barium sulfate to nano-ferrite in each layer of the second shielding layer into the simulation model in step S1.1 to test the shielding effect;
[0114] S1.7, determining whether the shielding effect meets the requirements, if yes, jumping to step S2, if not, returning to step S1.3 until the shielding effect meets the requirements.
[0115] In step S1.2, the gradient parameter optimization model includes:
[0116] 1. Parameter initialization: input total thickness (unit: mm); set the number of layers (default 10 layers); define the concentration of nano-barium sulfate in the first shielding layer (default 40%) and the concentration of nano-barium sulfate in the third shielding layer (default 25%);
[0117] 2. Standardization processing:
[0118] Divide the total thickness into the specified number of layers to generate a standardized coordinate axis from 0 to 1;
[0119] 3. Calculate the concentration gradient:
[0120] Determine the concentration span (a value) = maximum concentration - minimum concentration; set the attenuation coefficient (b value = 3.0) to control the gradient change rate; use the exponential decay formula: concentration value = a x e^(-b x standardized position) + minimum concentration;
[0121] 4. Position mapping: map the standardized position back to the actual thickness coordinate;
[0122] 5. Result output: return the actual position of each layer (retain 2 decimal places) and the corresponding concentration value (retain 2 decimal places).
[0123] Through this model, the material composition gradient transition from the first shielding layer to the third shielding layer is achieved through nonlinear exponential decay, and the attenuation coefficient b value can adjust the steepness of the gradient change, which is suitable for the design of functional gradient materials such as radiation shielding materials. Through this process, the best gradient slope can be determined to achieve a comprehensive shielding coefficient ≥0.98 in a 100 cm thick wall.
[0124] In step S1.2, the optimization ratio model includes:
[0125] 1. Layered optimization processing: traverse each functional layer of the gradient material; for each layer's specific energy spectrum characteristics (such as the proportion of different energy γ rays);
[0126] 2. Component ratio optimization: calculate the optimal ratio of the current layer through Monte Carlo simulation: a input: the expected energy spectrum data of the layer to be shielded; b output: the optimal mass ratio of nano-barium sulfate to Fe3O4; c considerations: photon interaction cross section, secondary radiation generation probability;
[0127] 3. Performance verification
[0128] The final output comprehensive shielding factor: a measured linear attenuation coefficient of the composite wall to 1 MeV γ rays; b verification of the design index of the linear attenuation coefficient.
[0129] This method realizes the coupling optimization of nano-barium sulfate concentration gradient and Fe3O4 magnetic performance, making the linear attenuation coefficient of the wall to 1 MeV γ rays reach 1.82 cm -1 .
[0130] In some embodiments, in order to be applicable to special scenarios that require protection against ionizing radiation and electromagnetic pulses at the same time, it is also necessary to adjust the optimization ratio in a synchronous manner to enable the cross-scale coupling of radiation shielding and electromagnetic properties: considering both nanoscale and macroscale at the same time.
[0131] The spatial distribution density of Fe3O4 particles and the applied electromagnetic field gradient parameters ensure that the magnetic field gradient matches the radiation shielding requirements.
[0132] In some embodiments, as a preference, the materials after the mixing of step S3 and step S4 are dispersed by ultrasonic assistance, specifically, the slurry Zeta potential absolute value is increased and the stability is improved by ultrasonic treatment with a frequency of 28 kHz and a power of 800 W.
[0133] In some embodiments, a multi-objective optimization model is constructed to further optimize the optimal mass ratio of nanometer barium sulfate and nanometer ferrite in each layer of the second shielding layer obtained in step S1.6 through the multi-objective optimization model, including:
[0134] 1. Parameter initialization phase
[0135] Set the basic parameters: including neutron energy spectrum distribution, total thickness requirement of concrete, material cost constraint conditions, etc.
[0136] Establish an initial optimization benchmark (such as uniform distribution or simple gradient distribution);
[0137] 2. Iterative optimization loop
[0138] Generate a candidate gradient scheme:
[0139] a. Generate a new gradient curve variant based on the current optimal solution;
[0140] b. Adjust the parameters including: number of layers, concentration gradient change rate, special additive distribution, etc.
[0141] 3. Shielding performance simulation
[0142] a. Input the detailed parameters of the candidate gradient scheme;
[0143] b. Calculate the transmittance of neutrons / gamma rays in different energy ranges;
[0144] c. Output the comprehensive shielding efficiency index;
[0145] 4. Multi-objective evaluation
[0146] Establish the Pareto front:
[0147] a. Horizontal axis: material cost (considering the amount of nanometer barium sulfate, fiber addition ratio, etc.);
[0148] b longitudinal axis: shielding efficiency (neutron / photon attenuation rate);
[0149] c dynamically updating the optimal solution set;
[0150] 5, convergence judgment
[0151] termination condition:
[0152] a the optimization amplitude of continuous N iterations is less than a threshold value;
[0153] b the maximum number of iterations is reached;
[0154] c the optimal solution that meets all the constraints is found;
[0155] 6, result output
[0156] return the final optimized gradient scheme:
[0157] a material ratio of each layer
[0158] b predicted shielding performance curve
[0159] c cost estimation report
[0160] By combining the multi-objective optimization method to balance the shielding performance and economy, the typical iteration number is about 50-200 times, which depends on the complexity of the parameter space. The design controls the concentration change rate at the interface to be less than or equal to 5wt% / cm by smoothing the concentration gradient, which significantly reduces the risk of local flocculation.
[0161]
[0162] The performance verification data of this embodiment is as follows:
[0163] Table 5 Performance verification data
[0164]
[0165] Through the above comprehensive measures, the effective dispersion and long-term stability of nanomaterials in the gradient structure can be ensured.
[0166] In some embodiments, the first material ratio is:
[0167] Gelled material: Portland cement 100 parts (reference), slag powder 30 parts, fly ash 15 parts (grade I ash, specific surface area ≥400m 2 / kg);
[0168] Radiation protection functional components: modified nano barium sulfate 38 parts (pretreated with silane coupling agent KH550); boron fiber 1.5 parts (diameter 6μm, length 12mm), nano silicon dioxide 2 parts (fumed, specific surface area 200±25m2 / g);
[0169] Aggregate: Barite sand 180 parts (2.36-4.75 mm continuous grading), steel slag fine aggregate 70 parts (density
[0170] ≥4.8 g / cm 3 , magnetic separation iron removal treatment);
[0171] Admixtures: Polycarboxylic acid water reducer 1.2 parts (solid content 40%), latex powder (VAE type) 0.8 parts, cellulose ether (HPMC) 0.05 parts (viscosity 40000 mPa·s);
[0172] The ratio of clean water to Portland cement is: clean water 32 parts (the ratio of clean water to Portland cement is 0.32, containing water reducer solution).
[0173] In some embodiments, the second material ratio is:
[0174] Binder: Portland cement 100 parts (reference), slag powder 23 parts, fly ash 15 parts (grade I ash, specific surface area ≥400 m 2 / kg);
[0175] Radiation protection functional components: modified nano ferrite (PVP modified) 2-5 parts; modified nano barium sulfate 38 parts (20 cm depth gradient decreasing design);
[0176] Aggregate: Barite sand 120 parts (2.36-4.75 mm continuous grading), steel slag fine aggregate 80 parts (density
[0177] ≥4.8 g / cm 3 , magnetic separation iron removal treatment);
[0178] Admixtures: Polycarboxylic acid water reducer 1.2 parts (water reducing rate ≥30%), silane coupling agent 0.3 parts (improve the interface bonding of nano barium sulfate);
[0179] The ratio of clean water to Portland cement is: clean water 32 parts (the ratio of clean water to Portland cement is 0.32, containing water reducer solution).
[0180] The modified nano ferrite (PVP modified) is preferably 3 parts, the particle size is 25-30 nm, and the PVP coating rate is ≥95%.
[0181] In some embodiments, the third material ratio is:
[0182] Binder: Portland cement 100 parts (reference), slag powder 20 parts, fly ash 15 parts (grade I ash, specific surface area ≥400 m 2 / kg);
[0183] Radiation protection functional components: high-density boron-containing polyethylene fiber 1.5 parts (diameter 20 μm, length 12 mm); modified nano-barium sulfate 25 parts;
[0184] Aggregate: barite coarse aggregate 150 parts (5-10 mm continuous gradation), machine-made sand 120 parts (fineness modulus 2.6-3.0);
[0185] Admixtures: polycarboxylic acid water reducer 1.5 parts (water-reducing rate ≥ 30%), latex powder 0.8 parts (ethylene-vinyl acetate copolymer);
[0186] The ratio of clean water to portland cement is 35 parts of clean water (the ratio of clean water to portland cement is 0.35).
[0187] In some embodiments, in step S3, the layered material uses a double-screw dynamic mixer, the barium sulfate content is controlled layer by layer, specifically by adjusting the screw speed (300-450 rpm), reducing the barium sulfate concentration according to an exponential function model, and synchronously injecting a composite water reducing agent to improve the fluidity.
[0188] In some embodiments, in step S3, uniform vibration is achieved by ultrasonic vibration reinforcement, a 20 kHz ultrasonic vibration plate is set, the vibration intensity is 0.5 W / cm 2 , and the duration is 5 min to eliminate particle agglomeration and promote interface bonding.
[0189] In some embodiments, in step S5, a vacuum spraying process is used to uniformly cover the first shielding layer concrete on the surface of the second shielding layer, the spraying distance is 200 mm, and the pressure is 0.3 MPa; immediately after spraying, ultraviolet curing (wavelength 365 nm, energy 800 mJ / cm 2 ) is performed to form a dense chemical cross-linking protective layer.
[0190] In some embodiments, in step S6, a staged steam curing process is used (third shielding layer 80℃ / 2h→ second shielding layer 60℃ / 3h→ first shielding layer 40℃ / 6h), the humidity is ≥ 90%, and the interlayer thermal stress is reduced by temperature difference control.
[0191] In some embodiments, in step S6, after curing, nano-SiO2 sol (0.5wt%) is injected to fill micro-cracks and improve the interlayer shear strength to ≥ 8 MPa.
[0192] In some embodiments, one of the following materials can be used to replace nano-ferrite Fe3O4: barium ferrite (BaFe 12 O 19 ), rare earth magnetic materials (such as neodymium iron boron), composite metal oxides (such as cobalt ferrite CoFe2O4), and lead-containing magnetic alloys.s
[0193] However, the best choice is Fe3O4, the raw material cost is only about 8-12 yuan / kg, the preparation difficulty is low, and the shielding performance is good. Compared with other neodymium iron boron and other rare earth materials, Fe3O4 has good advantages in preparation difficulty, economy and radiation shielding performance.
[0194] The radiation shielding body and the construction method thereof have the following technical effects:
[0195] 1. The radiation shielding body is provided with gradient-decreasing nano-barium sulfate, which can realize energy attenuation matching, and also has a multi-physical field synergistic mechanism. The neutron shielding gradient is: boron (first shielding layer) → nano-ferrite (second shielding layer) → fiber (third shielding layer), which forms a continuous capture-slowing-scattering chain. The electromagnetic field regulation: the nano-ferrite absorbs the secondary X-rays generated by the bremsstrahlung radiation through domain wall resonance.
[0196] 2. The doping amount of the nano-barium sulfate is regulated by gradient, combined with ultrasonic dispersion technology to ensure dispersibility, and the nano-ferrite is introduced to effectively enhance the radiation shielding effect of the concrete through the synergistic effect of the nano-ferrite and the nano-barium sulfate.
[0197] 3. The continuous gradient doping distribution of the nano-barium sulfate from the first shielding layer to the third shielding layer, and the refraction interface multiplication effect make the gamma ray attenuation efficiency improve.
[0198] 4. The ultrasonic-assisted second shielding layer forming (20 kHz / 0.5 W / cm 2 ) ensures the gradient continuity, and the interface shear strength is higher than that of the traditional lamination process.
[0199] 5. The radiation shielding effect of the radiation shielding body is verified by experiments, and it is found that compared with the existing radiation shielding concrete, the radiation shielding effect is improved when dealing with the dynamic shielding of the neutron-gamma mixed radiation field.
[0200] 6. The application range is wide, and it is suitable for scenes that need accurate radiation protection, such as nuclear power plant shielding walls, in addition to BNCT radiation scenes.
[0201] In the description of the present disclosure, it should be understood that the terms "center", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer" and the like indicate the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present disclosure and simplifying the description, and do not indicate or imply that the device or element referred to has a particular orientation, is constructed and operated in a particular orientation, and therefore cannot be understood as a limitation of the present disclosure.
[0202] Unless otherwise required by context, as used herein, the term "comprises" or "comprising" is understood to be an open rather than a limiting term, namely, in the sense that it is used to include, but not to exclude, the listed item as well as other like items. In the description of the embodiments of the application, the terms "one embodiment," "some embodiments,” "an exemplary embodiment,” “an example,” etc. do not necessarily refer to the same embodiment or example, but instead, can refer to a different embodiment or example. In addition, the described features, techniques, structures, and principles can be used in any number of embodiments or examples.
[0203] The terms "first", "second", etc. are used only to distinguish different described objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features, namely, the position, order, priority, number or content of the described objects. Therefore, the features limited by "first", "second" can explicitly or implicitly include one or more of the features. In the description of the embodiments of the present disclosure, the meaning of "a plurality of" is two or more, unless otherwise specified.
[0204] In describing some embodiments, the use of "connected" and / or "coupled" and / or terms of similar meaning can be used. For example, the term "connected" can be used to mean that two or more elements are in direct physical or electrical contact with each other. The embodiments disclosed herein are not necessarily limited to the context in which they are used.
[0205] "A, B, and C at least one of" has the same meaning as "at least one of A, B, or C", which includes the following combinations of A, B, and C: only A, only B, only C, a combination of A and B, a combination of A and C, a combination of B and C, and a combination of A, B, and C. In the description of the embodiments of the present application, unless otherwise specified, " / " means or, for example, A / B can mean A or B; "A and / or B" includes the following three combinations: only A, only B, and a combination of A and B.
[0206] The use of "configured to" herein means open and inclusive language that does not exclude devices that are adapted to perform additional tasks or steps.
[0207] In addition, the use of "based on" means open and inclusive, as the process, step, calculation or other action based on one or more described conditions or values can be based on additional conditions or values beyond those described in practice.
[0208] As used herein, "about," "approximately" include the recited value and the average value within an acceptable range of deviation from the particular value, as determined by one of ordinary skill in the art considering the measurement being discussed and the error in measuring the particular quantity (i.e., the limitations of the measurement system).
[0209] Exemplary embodiments are described herein with reference to cross-sectional and / or plan view illustrations that are idealized examples. In the drawings, the thickness of layers and regions are exaggerated for clarity. Accordingly, variations from the shapes of the illustrations as a result, for example, of manufacturing techniques and / or tolerances, are to be expected. Thus, exemplary embodiments should not be construed as limited to the particular shapes of regions as illustrated herein but are to include deviations in shapes that result, for example, from manufacturing. For example, an etched region illustrated as a rectangle will typically have rounded corners and / or uneven sidewalls as a result of manufacturing techniques and / or tolerances. Thus, the regions illustrated in the figures are schematic in nature and their shapes are not intended to illustrate the precise shape of a region of a device and are not intended to limit the scope of exemplary embodiments.
[0210] The above description is only specific implementation of the present disclosure, but the protection scope of the present disclosure is not limited thereto, and any person skilled in the art can think of changes or replacements within the technical scope disclosed by the present disclosure, which should be covered by the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be subject to the protection scope of the claims.
Claims
1. A radiation shielding method based on the synergistic effect of multiple physics fields, used to shield neutron-gamma mixed radiation fields, characterized in that, include: In the first stage, neutrons and gamma rays are absorbed at the initial radiation position by the first composite material; In the second stage, the first residual radiation after the first stage is attenuated by the second composite material through energy spectrum adaptation, and the amount of the second composite material decreases gradually along the radiation propagation direction. In the third stage, the second residual radiation that has passed through the second stage is path-scattered by a third composite material.
2. The radiation shielding method based on the synergistic effect of multiple physics fields according to claim 1, characterized in that, The first composite material includes a radiation shielding agent and a neutron absorber; in the first composite material, the mass ratio of the radiation shielding agent to the neutron absorber ranges from 10:1 to 45:
1.
3. The radiation shielding method based on the synergistic effect of multiple physics fields according to claim 1, characterized in that, The second composite material includes the radiation shielding agent and nano-ferrite; the nano-ferrite can be coupled to the surface of the radiation shielding agent; in the second composite material, the mass ratio of the radiation shielding agent to the nano-ferrite is in the range of 5:1 to 8:
1.
4. The radiation shielding method based on the synergistic effect of multiple physics fields according to claim 1, characterized in that, The third composite material includes the radiation shielding agent and the scattering fiber; in the third composite material, the mass ratio of the radiation shielding agent to the scattering fiber ranges from 10:1 to 30:
1.
5. The radiation shielding method based on the synergistic effect of multiple physics fields according to any one of claims 2 to 4, characterized in that, The radiation shielding agent is selected from one of barite, nano-barium sulfate particles, or modified nano-barium sulfate particles.
6. The radiation shielding method based on the synergistic effect of multiple physics fields according to any one of claims 2, characterized in that, The neutron absorber is selected from one of the following: boron inorganic salt, boron-containing organic matter, or boron fiber.
7. The radiation shielding method based on the synergistic effect of multiple physics fields according to claim 3, characterized in that, The nano-ferrite is a modified nanoparticle obtained by modifying a surface modifier; the surface modifier is one of polydopamine PDA, silane coupling agent, polyvinylpyrrolidone, and hexagonal boron nitride.
8. A radiation shield, constructed using the radiation shielding method based on the synergistic effect of multiple physics fields as described in claim 1, characterized in that, It includes a first shielding layer, a second shielding layer, and a third shielding layer arranged sequentially along the radiation propagation direction; The first shielding layer, the second shielding layer, and the third shielding layer are respectively doped with the first composite material, the second composite material, and the third composite material; The first composite material includes a radiation shielding agent and a neutron absorber; The second composite material includes the radiation shielding agent and nano-ferrite; The third composite material includes the radiation shielding agent and the scattering fiber; The second shielding layer is a multi-layer structure, with each layer being doped with the second composite material. The amount of the second composite material doped in each layer decreases gradually along the radiation propagation direction.
9. The radiation shielding body according to claim 8, characterized in that, In the first shielding layer, the first doping amount of the radiation shielding agent is in the range of 32 to 44 wt%, and the mass ratio of the radiation shielding agent to the neutron absorber is in the range of 10:1 to 45:
1. In the second shielding layer, the nano-ferrite can be coupled to the surface of the radiation shielding agent; the amount of radiation shielding agent in the first layer of the second shielding layer near the first shielding layer is less than or equal to the first amount; in each layer structure of the second shielding layer, the rate of change of the radiation shielding agent content gradient between two adjacent layers is ≤5wt% / cm, and the mass ratio of the radiation shielding agent to the nano-ferrite is in the range of 5:1 to 8:1; In the third shielding layer, the second doping amount of the radiation shielding agent ranges from 20 to 30 wt%, and the mass ratio of the radiation shielding agent to the scattering fiber ranges from 10:1 to 30:1; the first doping amount is greater than the second doping amount, and the doping amount of the radiation shielding agent in the last layer of the second shielding layer near the third shielding layer is greater than or equal to the second doping amount.
10. The radiation shielding body according to claim 8 or 9, characterized in that, The thickness of the first shielding layer is 0-10cm, the thickness of the second shielding layer is 10-30cm, and the total number of layers n of the second shielding layer is 5-20. The thickness of the third shielding layer is ≥30cm.
Citation Information
Cited By
Radiation shielding material and method for manufacturing radiation shielding material
JP7891306B1